Anthropometric Profile of Children Attending Anganwadi Centers under Integrated Child Development Sevices (ICDS) Scheme in Doiwala Block - Kaur, Gagan Deep; Aggarwal, Pradeep; Kakkar, Rakesh (Indian Journal of Community Health, 2014)
Introduction In any community, Mothers and Children constitutes not only priority group, but they are also a “Vulnerable” or “Special-risk Group”. Similarly in India our biggest problem is malnutrition among under five year old children. To break the vicious cycle of malnutrition, morbidity reduced learning capacity and mortality India launched the Integrated Child Development Services (ICDS) Scheme in 1975. It is the foremost symbol of India’s commitment to her children Rationale: Forty percent of the world's severely under-nourished under-five children live in India so the present study was conducted to assess the nutritional status of children availing the services under Integrated Child Development Service Scheme in Uttarakhand. Objective: To estimate the level of nutrition in children attending Anganwadi centers of Doiwala block. Methods: Out of these Seven ICDS project areas, Doiwala Block was chosen for the study purpose since it is also the field practice area of Department of Community Medicine, HIMS. 19 AWC was selected by using Simple Random Sampling technique in Doiwala block. All the children aged between 3- 6years attending Anganwadi centers were included in community based, cross sectional study. Predesigned pretested anthropometric survey tool with local adaptability and minor modification for local suitability was adopted to collect information pertaining to growth monitoring of the children [Adopted from WHO child growth standard 2006]. Children were weighed, and their height and MUAC were recorded. Weight for age, height for age and MUAC for age was calculated using WHO growth references .Nutritional status according to the WHO Child Growth Standards was analysed using WHO Anthro statistical software. Results: 200 children were surveyed. From the total population 110 are males and 90 are females. After the analysis of weight for age with anthro software it was found that 20.9% of children lie within -2 SD with a mean of -0.98 and SD of 1.14.In case of height for age 30.9% of children lie within -2 SD with a mean of -0.92 and SD 1.87.BMI for age 25.8% of children lie within -2SD with a mean of-1.58 and SD1.3.MUAC for age 30% of children lie within -2SD. Conclusion: As per anthropometric calculation the burden of malnutrition was high among children attending Anganwadi centers. This raises concern about the children who are not allowed to attend the Anganwadi centers on regular basis due to various reasons. Burden of malnutrition among children attending Anganwadi centers can be tackled by enhancing the quality of mid-day meal programme especially on high protein and caloric intake.